Blended Learning For English Language Teaching (ELT) Classroom In Higher Education - Badaruddin, Badaruddin; Basri, Muhammad; Ziska, Ika Yanti; Hasman, Hasman (CV. Rayyan Dwi Bharata, 2025)
To meet the requirements of the fourth industrial revolution, education plays a critical role in creating skilled and marketable human capital, so an instructional model that promotes student self-directed learning is needed. The digital era has had a major effect on English Language Teaching (ELT), allowing teachers to perform distance or combined learning. Blended learning is a learning model that focuses on promoting student individuality through the usage of various mobile technologies. Consequently, The purpose of this research is to provide information about an instructional template for a new blended learning model that uses the ADDIE model to help students develop self-directed learning. The ADDIE model is a modular framework that includes all of the required elements for creating effective ELT instruction. This study was conducted in Universitas Muhammadiyah Parepare. This paper also discusses a number of modern technologies that enable students to obtain individualized attention and new learning opportunities. As a result of this research, a new blended learning model has been developed to assist students in developing self-directed learning skills in English through the use of a variety of modern technologies.